Multinational companies in the EU and European Works Councils - Christoph Dörrenbächer; Michael Wortmann (Intereconomics, 1994)
In June the EU Council of Ministers (excluding the UK) took up a common position concerning European Works Councils. The establishment of such Councils would grant certain information and consultation rights to the workers of multinational companies. The following paper looks at the importance of MNCs in the EU and tries to assess the extent to which European Works Councils could cope with the social problems arising in these MNCs.
Keywords: 330